Characteristic Squalene compounds Shark Liver Oil of home industry product in Pelabuhan Ratu - Sri Ayu Insani; Sugeng Heri Suseno; Agoes Mardiono Jacoeb (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Omega-3, omega-6, omega-9 fatty acids and Squalene are active components of fish oil that arebeneficial to human health. Squalene is mostly contained in shark liver oil (Centrophorus sp.). The aimof this research was to determine the quality and characteristics of shark fish oil of household productionin Pelabuhan Ratu. The analyses performed were to determine fatty acid profile, primary and secondaryoxidation and characteristics of squalene contained in the shark liver oil. The fatty acid profile showedthat the dominant fatty acids of shark liver oil were oleic acid (28.22%), Eicosapentaenoic Acid (1.54%)and Docosahexaenoic Acid (4.78%). The results of primary and secondary oxidation measurement showedshark liver oil contained a high oxidation value of PV (17.73 mEg/kg), p-AV (29.32 mEg/kg), TOTOX(64.78 mEg/kg) and FFA (4.65%). The values of density and viscosity of the shark liver oil 0.91 g/cm3 and38.18 cPs. Clarity of shark liver oil at a wavelength of 450 nm was 84.98%. GC-MS chromatogram showedthat squalene peak appears at the retention time of 23.357 with a total area of 12.49% and its molecularweight was 410.391 g/mol.